Phosphatidylinositol 4-Phosphate 5-Kinases in the Regulation of T Cell Activation - Porciello, Nicla; Kunkl, Martina; Viola, Antonella; Tuosto, Loretta (Frontiers in Immunology, 2016)
Phosphatidylinositol 4,5-biphosphate kinases (PIP5K) are critical regulators of T cell activation being the main enzymes involved in the synthesis of phosphatidylinositol 4,5-biphosphate (PIP2). PIP2 is indeed a pivotal regulator of the actin cytoskeleton, thus controlling T cell polarization and migration, stable adhesion to antigen presenting cells (APC), spatial organization of the immunological synapse (IS), and costimulation. Moreover, PIP2 serves also as a precursor for the second messengers inositol triphosphate (IP3), diacylglycerol (DAG) and phosphatidylinositol 3,4,5-triphosphate (PIP3), which are essential for the activation of signalling pathways regulating cytokine production, cell cycle progression, survival, metabolism and differentiation. Here, we discuss the impact of PIP5Ks on several T lymphocyte functions with a specific focus on the role of CD28 co-stimulation in PIP5K compartimentalization and activation.